Perforating Sclerosing Mesenteritis of the Colon Mimicking A Tumor: Autopsy Case Report and Mini-Review - Gaggero G.; Valle L.; Ferro J.; Taietti D. (Acta Medica Bulgarica)
Aim and subject. Sclerosing mesenteritis is a rare non-tumoral disease that usually affects the small intestine.Several etiological hypotheses have been proposed (external or surgical trauma, autoimmunity, neoplasia).